ASSESSING LISTENING IN THE LANGUAGE CLASSROOM - Kristanti Ayuanita (IAIN MADURA, 2013)
The importance of listening in language learning can hardly be overestimated. In classrooms, students always do more listening than speaking. Listening competence is universally “larger” than other competence. Listening is not a oneway street. It is not merely the process of a unidirectional receiving of audible symbols one facet – the first step – 0f listening comprehension is the psychomotor process of receiving sound waves through the ear and transmitting nerve impulses to the brain. Every classroom lesson involves some form of assessment, whether it is in the form of informal, unplanned, and intuitive teacher processing and feedback, or in formal, prepared, scored tests.